2014
DOI: 10.3109/14767058.2014.880879
|View full text |Cite
|
Sign up to set email alerts
|

Correlation analysis between echocardiographic flow pattern and N-terminal-pro-brain natriuretic peptide for early targeted treatment of patent ductus arteriosus

Abstract: NT-proBNP concentrations at T0 show a good agreement with different flow patterns and represent a useful tool to identify neonates at risk of developing hemodynamically significant PDA.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
7
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(9 citation statements)
references
References 24 publications
2
7
0
Order By: Relevance
“…In our study, no infants developed clinical sepsis during the first week of life; high levels of NT-proBNP are only reflection of PDA status. Our results regarding heart geometry in PDA infants are also in agreement with Occhipinti et al 30 as NT-proBNP plasma concentrations are related to ductal size and left atrial dilatation in preterm infants during the first days after birth. LA/Ao ratio, in our study, correlated with the plasma NT-proBNP level after adjusting for other related variables.…”
Section: Discussionsupporting
confidence: 92%
“…In our study, no infants developed clinical sepsis during the first week of life; high levels of NT-proBNP are only reflection of PDA status. Our results regarding heart geometry in PDA infants are also in agreement with Occhipinti et al 30 as NT-proBNP plasma concentrations are related to ductal size and left atrial dilatation in preterm infants during the first days after birth. LA/Ao ratio, in our study, correlated with the plasma NT-proBNP level after adjusting for other related variables.…”
Section: Discussionsupporting
confidence: 92%
“…ProBNP, the inactive precursor, is cleaved into BNP, the active component, and Nterminal pro -BNP (NT -proBNP), an inactive byproduct. Plasma concentrations of BNP correspond well with echocardiographic findings of ventricular strain 2) . Plasma NT -proBNP is very high during the first few days of life in healthy neonates, decreases rapidly until the end of the first week of life, and then decreases slowly until the end of the neonatal period 3 -5) .…”
Section: Introductionsupporting
confidence: 70%
“…To the best of our knowledge, studies of NT -proBNP in neonatal diseases have been reported as the serial changes of NT -proBNP in the pathologies of respiratory distress syndrome 14) , transient tachypnea of the newborn 15,16) , persistent ductus arteriosus 2,17) , persistent pulmonary hypertension 18,19) , bronchopulmonary dysplasia 20,21) and asphyxia 22) . However, our patient had none of these diseases.…”
Section: Discussionmentioning
confidence: 99%
“…A recent meta‐analysis found NT‐proBNP to be a more sensitive, but less specific marker for hsPDA than brain natriuretic peptide, a similar marker of atrial dilatation that has been used as a biomarker for cardiac dysfunction due to PDA . NT‐proBNP has been shown to have good correlation with flow patterns on echocardiography that are associated with hemodynamic significance of the PDA . Recent work by Rodríguez‐Blanco et al suggests that for the prediction of BPD, NT‐proBNP may be a superior measure of an hsPDA than echocardiography because increased NT‐proBNP levels more accurately predicted the development of BPD than did the detection of an hsPDA by echocardiography alone.…”
Section: Hemodynamically Significant Pda and Bpdmentioning
confidence: 99%
“…25 NT-proBNP has been shown to have good correlation with flow patterns on echocardiography that are associated with hemodynamic significance of the PDA. 26 Recent work by Rodríguez-Blanco et al 27 suggests that for the prediction of BPD, NT-proBNP may be a superior measure of an hsPDA than echocardiography because increased NT-proBNP levels more accurately predicted the development of BPD than did the detection of an hsPDA by echocardiography alone. This relationship may explain earlier work suggesting NT-proBNP is an independent biomarker of BPD development.…”
Section: Hemodynamic Ally S Ig Nific Ant Pda and B Pdmentioning
confidence: 99%